Increased thalamocortical connectivity to the medial prefrontal cortex with recovery of impaired consciousness in a stroke patient: A case report - Jang, Sung Ho (Medicine (Baltimore), 2020)
RATIONALE: We report a stroke patient who showed increased thalamocortical connectivity to the medial prefrontal cortex (mPFC) with recovery of impaired consciousness that was demonstrated on diffusion tensor tractography (DTT) of the ascending reticular activating system (ARAS). PATIENTS CONCERNS: A 48-year-old male patient underwent craniectomy and hematoma removal for spontaneous intracerebral hemorrhage in the right basal ganglia and thalamus. When he started rehabilitation at 5 weeks after onset he was in a vegetative state with a Coma Recovery Scale-Revised score of 6. DIAGNOSES: The patient was diagnosed spontaneous intracerebral hemorrhage in the right basal ganglia and thalamus. INTERVENTIONS: He underwent comprehensive rehabilitation including neurotropic durgs, transcranial direct current stimulation, and repetitive transcranial magnetic stimulation of the left prefrontal lobe (Brodmann area 10). OUTCOMES: After 5 weeks of rehabilitation, the patient had recovered to a nearly normal conscious state with a Coma Recovery Scale-Revised score of 22. On 10-week DTT, thickening of the lower dorsal ARAS was observed on both sides compared with 5-week DTT. Decreased neural connectivity to the left PFC was observed on 5-week DTT whereas decreased neural connectivity to the left PFC was increased on 10-week DTT, especially the mPFC. LESSONS: Increased thalamocortical connectivity to the mPFC was demonstrated in a stroke patient who showed concomitant recovery from a vegetative state to a nearly normal conscious state. The results suggest that the increased neural connectivity to the mPMC contributed to recovery of consciousness in this patient.